2007
DOI: 10.1371/journal.pntd.0000072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Selection of Low Fertile Onchocerca volvulus by Ivermectin Treatment

Abstract: Background Onchocerca volvulus is the causative agent of onchocerciasis, or “river blindness”. Ivermectin has been used for mass treatment of onchocerciasis for up to 18 years, and recently there have been reports of poor parasitological responses to the drug. Should ivermectin resistance be developing, it would have a genetic basis. We monitored genetic changes in parasites obtained from the same patients before use of ivermectin and following different levels of ivermectin exposure.Methods and Findings O. vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 28 publications
(57 reference statements)
2
62
0
2
Order By: Relevance
“…This assumption is based on lack of published evidence for heterogeneity in life-history parameters of O. volvulus (e.g., differences in life expectancy)-but see recent work by Bourguinat et al (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is based on lack of published evidence for heterogeneity in life-history parameters of O. volvulus (e.g., differences in life expectancy)-but see recent work by Bourguinat et al (32).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the host's skin repopulation rate provides a method of quantifying an individual host's response to treatment which can be correlated with the genotypic information of parasites obtained from that host (microfilariae and adult worms). A number of possible molecular markers (including beta-tubulin and Pglycoprotein among others) have been identified which could provide useful tools in identifying anthelmintic resistance before it becomes widely spread (32,33). Linking phenotypic responses with molecular genetics markers will be required to prove that suboptimal responses are in fact due to drug-resistant parasites and not to host-related factors (3).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline may also be developed as a reserve drug if the concerns regarding the potential development of ivermectin resistance (Bourguinat et al 2007;Osei-Atweneboana et al 2007) are proven to be correct and quick action is needed to prevent spreading of resistant worms. Finally, anti-wolbachial chemotherapy may become an option for areas that are co-endemic for loiasis and where ivermectin treatment has resulted in the occurrence of encephalopathy (Thomson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been reported that some populations of the intestinal nematode Haemonchus contortus in sheep have developed a certain degree of ivermectin resistance (Coles et al 2005). Since genetic selection of low fertile Onchocerca volvulus by ivermectin treatment has been observed, it was hypothesized that O. volvulus populations more tolerant to ivermectin may also be selected (Bourguinat et al 2007). Epidemiological hints for a suboptimal performance of ivermectin against O. volvulus populations have been detected in northern Ghana (Awadzi et al 2004a,b;Osei-Atweneboana et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These observations may indicate a reduced embryostatic effect of the drug in some patients. In addition, it has been shown that IVM induces a selection for the P-glycoprotein (PgP), P-glycoprotein-like protein (PLP) and β-tubulin genes in adult worms, and that a relationship exists between the genotype of the adult worms for the β-tubulin gene and their fertility (Prichard, 2007;Bourguinat et al, 2007). These results are a matter of concern, even if it has also been shown that IVM remains as efficient on O. volvulus mfs (the pathogenic stage) as it was 20 years ago.…”
Section: The Possible Emergence Of Ivermectin Resistance In O Volvulusmentioning
confidence: 99%